2024
DOI: 10.1021/acsabm.4c00028
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered Salivary Gland Microtissues─A Review of 3D Cellular Models and their Applications

Sangeeth Pillai,
Jose G. Munguia-Lopez,
Simon D. Tran

Abstract: Salivary glands (SGs) play a vital role in maintaining oral health through the production and release of saliva. Injury to SGs can lead to gland hypofunction and a decrease in saliva secretion manifesting as xerostomia. While symptomatic treatments for xerostomia exist, effective permanent solutions are still lacking, emphasizing the need for innovative approaches. Significant progress has been made in the field of three-dimensional (3D) SG bioengineering for applications in gland regeneration. This has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…Stem cells are a proven resource in tissue engineering because of their remarkable potential to differentiate into different cell lineages [ 3 , 9 ]. Both adult and embryonic salivary gland-derived cells have demonstrated key in vitro characteristics essential for constructing 3D models of salivary glands [ 20 ]. Dental pulp stem cells, classified as adult stem cells, offer distinct advantages as they can be easily obtained from extracted teeth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cells are a proven resource in tissue engineering because of their remarkable potential to differentiate into different cell lineages [ 3 , 9 ]. Both adult and embryonic salivary gland-derived cells have demonstrated key in vitro characteristics essential for constructing 3D models of salivary glands [ 20 ]. Dental pulp stem cells, classified as adult stem cells, offer distinct advantages as they can be easily obtained from extracted teeth.…”
Section: Resultsmentioning
confidence: 99%
“…Spheroids derived from oral mucosa have found utility in various oral disease models, with specific gingival spheroids serving as valuable tools for studying gingiva–bacteria interactions [ 24 ]. In the realm of salivary gland research, spheroids and organoids have emerged as indispensable platforms for investigating glandular pathophysiology [ 20 ]. These 3D culture models provide insights into optimal culture conditions and biomaterials conducive to the organization of dental stem cells (DSCs).…”
Section: Resultsmentioning
confidence: 99%
“…In today’s fast-paced world of life science and biomedical research, a large body of experimental evidence has clearly demonstrated the enormous potential of three-dimensional (3D) cell cultures for improving our understanding of cell biology and the molecular mechanisms underlying disease [ 1 , 2 , 3 ], for drugs development and testing [ 4 , 5 , 6 , 7 ], in regenerative medicine [ 8 , 9 ] and also in tissue engineering [ 1 ]. Research has focused heavily on developing protocols and fine-tuning new technological approaches to developing diverse 3D in vitro models, also in agreement with the 3Rs (Replacement, Reduction, Refinement) principles of the European Union [ 10 ].…”
Section: Introductionmentioning
confidence: 99%